Ronnarong plīanplǣng thōt prahān chīwit tām lak sitthi manutsayachon sākon : ʻēkkasān thāng wichākān - Čhilāphō̜n Tāmchū; Ānon Yangkhun (Kō̜ng Songsœ̄m Sitthi læ Sērīphāp, Krom Khumkhrō̜ng Sitthi læ Sērīphāp, Krasūang Yuttitham, 2014)
Capital punishment and the death penalty in various countries and in Thailand.